Success in Consulting. Issue 9 (October 2015) - Adams, Kathryn Sulloway; Moore, Andrea; Roux‐Zink, Mary Rita; Wykes, L. Michael; Kearny, Lynn
<x xml:space="preserve">Abstract</x> Do you regularly reflect on the value you bring to your client? The act of reflection is something experienced consultants, both internal and external, consistently do in their practice. This article examines the ways in which Certified Performance Technologists (CPTs) define and recognize the success of their efforts, but most importantly, how they learn from engagements that do not always end with the desired outcome. You will hear from CPTs across several industries in their own words about what strategies they have employed to continue to improve their skill sets.